Implementing Externally Induced Innovations: A Comparison of Rule-Bound and Autonomous Approaches - Marcus, Alfred A. (Academy of Management Journal, 1988)
This research analyzed how nuclear power plants implemented safety review innovations introduced by the Nuclear Regulatory Commission after the Three Mile Island accident. The findings suggested that nuclear power plants with relatively poor safety records tended to respond in a rule-bound manner that perpetuated their poor safety performance and that nuclear power plants whose safety records were relatively strong tended to retain their autonomy, a response that reinforced their strong safety performance.